Longitudinal associations of social cognition and substance use in childhood and early adolescence: findings from the Avon Longitudinal Study of Parents and Children. - Fluharty, Meg E.; Heron, Jon; Munafò, Marcus R. (European Child & Adolescent Psychiatry, 2018)
Substance use is associated with impaired social cognition. Experimental studies have shown that acute intoxication of alcohol, tobacco, and cannabis decreases the performance in non-verbal, social communication and theory of mind tasks. However, in epidemiological studies the temporal direction of this association has gone relatively unstudied. We investigated both directions of association within an adolescent birth cohort: the association of social cognition with subsequent substance use, and the association of early substance use with subsequent social cognition. We used data from the Avon Longitudinal Study of Parents and Children, a UK birth cohort. Logistic regression indicated that poor childhood non-verbal communication was associated with decreased odds of adolescent alcohol (OR 0.70, 95% 0.54-0.91), tobacco (OR 0.62, 95% CI 0.47-0.83), and cannabis use (OR 0.62, 95% CI 0.46-0.83). Early adolescent substance use was associated with increased odds of poor social communication (alcohol: OR 1.46, 95% CI 0.99-2.14; tobacco: OR 1.95, 95% CI 1.33-2.86) and poor social reciprocity (alcohol: OR 1.57, 95% CI 1.18-2.09; tobacco: OR 1.92, 95% CI 1.43-2.58; cannabis: OR 1.54, 95% CI 1.16-2.05). Overall, the relationship between social cognition and substance use was different in each temporal direction. Poor non-verbal communication in childhood appeared protective against later substance use, while adolescent substance use was associated with decreased social cognitive performance.